RELIGION, WILLIAM E . PADEN DAN KEBERAGAMAAN DI INDONESIA - AINUL CHURRIA ALMALACHIM (Jurnal Ilmiah Ilmu Ushuluddin, 2020)
This paper examines how to view the religion of William E. Paden's perspective in his work entitled "Interpreting The Sacred: Ways Of Viewing Religion". In this discussion, one of the most important contemporary thinkers with a new comparative approach, based on the hermeneutic approach and creating a broad scope for cross-culture, the comparison of the forms of religiosity, is the American philosopher and religious theorist, William E. Paden (1939). He showed that the religion with proper terms such as Islam, Catholicism, Protestantism, Hinduism and Buddhism was very easy, but what was most basic was what was the abstract form of the various religions? In his book Interpreting the Sacred: Ways of Viewing Religion this Paden offers a method of viewing religion through interpretations that are full of frames from interpreters